2002
DOI: 10.1046/j.1466-822x.2002.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of vascular plant species richness and endemic richness along the Himalayan elevation gradient in Nepal

Abstract: Aim Species richness and endemic richness vary along elevation gradients, but not necessarily in the same way. This study tests if the maxima in gamma diversity for flowering plants and the endemic subset of these plants are coherent or not. LocationThe study was conducted in Nepal, between 1000 and 5000 m a.s.l. MethodsWe used published data on distribution and elevational ranges of the Nepalese flora to interpolate presence between maximum and minimum elevations. Correlation, regression and graphical analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
345
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(389 citation statements)
references
References 46 publications
37
345
2
5
Order By: Relevance
“…Species richness increased linearly with elevation. This is not consistent with other studies where species richness decreases monotonically (Stevens, 1992) or shows a hump-backed pattern along elevation gradients (Rahbek, 1995;Vetaas and Grytnes, 2002). Our elevation gradient only covered 300 m, but the posi-FIGURE 2.…”
Section: Species Richness and Evennesscontrasting
confidence: 92%
See 2 more Smart Citations
“…Species richness increased linearly with elevation. This is not consistent with other studies where species richness decreases monotonically (Stevens, 1992) or shows a hump-backed pattern along elevation gradients (Rahbek, 1995;Vetaas and Grytnes, 2002). Our elevation gradient only covered 300 m, but the posi-FIGURE 2.…”
Section: Species Richness and Evennesscontrasting
confidence: 92%
“…tion of the gradient (4800-5105 m) was well above the elevation at which the maximum number of species occurred in other alpine regions located in a similar latitudinal range (Vetaas and Grytnes, 2002;Tang et al, 2006;Wang et al, 2007). Thus, we would expect a decreasing rather than increasing trend of species richness with altitude.…”
Section: Species Richness and Evennessmentioning
confidence: 85%
See 1 more Smart Citation
“…Between 1,500 and 2500 m, little change in the number of species has been observed, but above this altitude, a decrease in species richness is evident (Vetaas and Grytnes, 2002). The results of this study also reflect this general trend found in plant diversity of mountain forests in Himalaya.…”
Section: Tree Diversitysupporting
confidence: 82%
“…More phytogeographically widespread species are confined mainly to lower altitudes while wetland sites at higher altitudes, (with higher soil organic matter content), contain more endemic and other geographically-restricted taxa. The increase in endemism with increasing altitude is consistent with 84 A. Kamrani et al 17.5*** other wetland or terrestrial studies (Kessler 2000;Vetaas & Grytnes 2002;Hájek et al 2008;Noroozi et al 2008;Naqinezhad et al 2009). Many of wetland species, ca.…”
Section: Discussionsupporting
confidence: 85%